Anatomical study of canthal index: The morphometrical study - Yadav, Sanjay Kumar; Malla, Banshi Krishna; Srivastava, Ashok Kumar; Kumar, Alok (Journal of Kathmandu Medical College, 2020)
Background: Anthropometry is the hallmark technique for biological anthropometry and has become increasingly important in health assessment across this century. Craniofacial anthropometry is study of face and skull. The local data on inner canthal distance, outer canthal distance and canthal index may signify the differential developmental pattern resulting from various factors such as gender, age, genetic and climate and may help in craniofacial surgery, orthodontists, congenital anomalies and forensic science.Objectives: The objective of the study is to compare anthropometric dimension related to inner canthal distance, outer canthal distance and canthal index.Methodology: The outer and inner canthal measurements of Nepali population wereobserved in 318 normal male and female. Out of total samples, 156 male and 162 female of age 17 – 25 years were taken for study since study was done in medical college preclinical students. The inner and outer canthal distances were measured by using a digital sliding caliper graduated in millimeters. The canthal index was calculated.Results: There was statistically significant difference in inner canthal distance among female (31.84± 2.22)mm and male (34.48 ±3.35)mm (P